SOCIO-PSYCHOLOGICAL CHARACTERISTICS OF FAMILY ROLES AND SELF-ATTITUDE AMONG WOMEN (A COMPARATIVE STUDY OF PUBLIC AND PRIVATE PRESCHOOL EDUCATIONAL INSTITUTIONS) (Eureka Journal of Education & Learning Technologies, 2026)
The family represents one of the most fundamental social institutions, playing a decisive role in shaping an individual's psychological well-being, social adaptation, and personal development. Contemporary socio-economic transformations have substantially altered traditional family structures, resulting in changes in family role distribution and women's psychological functioning within the family system. The present study aims to comparatively investigate the socio-psychological characteristics of family role distribution and self-attitude among women whose children attend public and private preschool educational institutions.The study involved 110 female participants, including 52 mothers whose children attended public preschool institutions and 58 mothers whose children attended private preschool institutions. Two standardized psychological instruments were employed: the Family Role Distribution Questionnaire developed by Y. Aleshina and L. Gozman and the Self-Attitude Inventory developed by V.V. Stolin and S.R. Panteleev. Statistical analyses were conducted using IBM SPSS Statistics, with group differences examined through the Independent Samples Student's t-test.
Keywords: Women, family roles, self-attitude, family psychology, preschool education, socio-psychological characteristics, parenting, psychological well-being, family relationships, empirical research.